2003
DOI: 10.1242/dev.00391
|View full text |Cite
|
Sign up to set email alerts
|

A novel function forHedgehogsignalling in retinal pigment epithelium differentiation

Abstract: Sonic hedgehog is involved in eye field separation along the proximodistal axis. We show that Hh signalling continues to be important in defining aspects of the proximodistal axis as the optic vesicle and optic cup mature. We show that two other Hedgehog proteins, Banded hedgehog and Cephalic hedgehog, related to the mouse Indian hedgehog and Desert hedgehog, respectively, are strongly expressed in the central retinal pigment epithelium but excluded from the peripheral pigment epithelium surrounding the ciliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
129
0
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 70 publications
(99 reference statements)
23
129
0
9
Order By: Relevance
“…Previous studies have implicated hedgehog signaling in retinal progenitor proliferation (Jensen and Wallace, 1997;Levine et al, 1997;Wang et al, 2002;Perron et al, 2003) In this study, we have found that ptcϩ/Ϫ mice show two abnormalities in cell proliferation. First, the ptcϩ/Ϫ mice have a significant increase in the number of proliferating cells at postnatal ages when predominantly late-born retinal cell types are differentiating.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have implicated hedgehog signaling in retinal progenitor proliferation (Jensen and Wallace, 1997;Levine et al, 1997;Wang et al, 2002;Perron et al, 2003) In this study, we have found that ptcϩ/Ϫ mice show two abnormalities in cell proliferation. First, the ptcϩ/Ϫ mice have a significant increase in the number of proliferating cells at postnatal ages when predominantly late-born retinal cell types are differentiating.…”
Section: Discussionsupporting
confidence: 56%
“…Lineage studies suggest that a slowly dividing more primitive stem cell is located far peripherally and capable of producing all retinal cell types as well as pigmented epithelial cells, and that faster cycling, more fate-restricted progenitor cells are located immediately adjacent to the retinal margin (Wetts et al, 1989). More recent work in the frog eye has directly shown expression of Shh signaling molecules in the CMZ, strongly implicating this signaling system in adult retinal proliferation in amphibians (Perron et al, 2003).…”
Section: The Role Of Ptc In the Cmzmentioning
confidence: 99%
“…In the chicken retina, in vivo studies show that Shh signaling is responsible for turning on genes specific to the ventral optic cup (Zhang and Yang, 2001b). Shh signal transduction molecules are expressed in the anterior margin of the retina responsible for postembryonic retinal growth in Xenopus laevis, the ciliary marginal zone (CMZ) (Perron et al, 2003), but their role in the CMZ has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…The defective vOS development of Shh-deficient mice can be partially rescued by concomitant loss of the Gli3 (GLI family zinc finger 3) allele, suggesting that the transcriptional regulation of Hh target genes is critical for vOS development (Furimsky and Wallace, 2006;Kim and Lemke, 2006). Supporting this hypothesis, the expression of genes important for vOS development, such as Pax2 (paired box gene 2) and ventral anterior homeobox 1 (Vax1), is induced by Shh, whereas retinal determining genes, such as Pax6 and Rx/Rax (retina and anterior neural fold homeobox), are repressed by ectopically expressed Shh (Perron et al, 2003). Shh not only ventralizes the OV through transcriptional activation of OS determinants, it also regulates them at the post-translational level.…”
Section: Wntsmentioning
confidence: 92%
“…Hedgehog (Hh) signaling originating from the ventral forebrain has therefore been implicated in the specification of the ventral and proximal optic structure (i.e., vOS), but inhibits dorsal-distal fate (i.e., NR and RPE). Indeed, genetic elimination of Shh in mice and chemical inhibition of Hh signaling in Xenopus embryos impairs vOS development, resulting in proximal-distal patterning defects (Chiang et al, 1996;Perron et al, 2003). The defective vOS development of Shh-deficient mice can be partially rescued by concomitant loss of the Gli3 (GLI family zinc finger 3) allele, suggesting that the transcriptional regulation of Hh target genes is critical for vOS development (Furimsky and Wallace, 2006;Kim and Lemke, 2006).…”
Section: Wntsmentioning
confidence: 99%